A Scientometric Review Of Medical Publications Related To Cerebrovascular Diseases And Economic Burdens Worldwide - Adzly Hairee Sahabudin; Amirah Azzeri; Mohd Noor Afiq Ramlee; Mohd Iqbal Mohd Noor; Amira Mas Ayu Amir Mustafa; Mohd Hafiz Jaafar (Persatuan Pakar Perubatan Kesihatan Awam Malaysia, 2024)
Indexed by Scopus